Complex elbow instability: surgical management of elbow fracture dislocations. Issue 5 (May 2016) - Sanchez-Sotelo, Joaquín; Morrey, Mark
Abstract : There are three main patterns of complex elbow instability: posterolateral (terrible triad), varus posteromedial (anteromedial coronoid fracture with lateral collateral ligament complex disruption), and trans-olecranon fracture dislocations. Radial head fractures, in the setting of complex elbow instability, often require internal fixation or arthroplasty; the outcome of radial head replacement is dictated by adequate selection of the head diameter, correct restoration of radial length, and proper alignment and tracking. Small coronoid fractures can be ignored. Larger coronoid fractures, especially those involving the anteromedial facet, require fixation or graft reconstruction, particularly in the presence of incongruity. The lateral collateral ligament complex should be repaired whenever disrupted. Medial collateral ligament disruptions seem to heal reliably without surgical repair provided all other involved structures are addressed. The most common mistakes in the management of trans-olecranon fracture dislocations are suboptimal fixation, lack of fixation of coronoid fragments, and lack of restoration of the natural dorsal angulation of the ulna. Cite this article: Sanchez-Sotelo J, Morrey M. Complex elbow instability. EFORT Open Rev 2016;1:183-190.